Complete labial fusion causing pseudo-urinary incontinence: A long-term sequelae of genitourinary syndrome - Tanvir Tanvir; Meeta Meeta; Akanshi Singh (Wolters Kluwer Medknow Publications, 2020)
Genitourinary syndrome (GSM) of menopause is due to hypoestrogenism affecting the vagina and lower urinary tract. Atrophic changes manifesting as complete labial fusion (CLF) are rare. They may present with urinary incontinence and cannot be classified as stress or urge urinary incontinence. We report a case of 68-year-old postmenopausal women who presented with symptoms of urinary incontinence secondary to CLF. Surgical correction and restoration of the labial anatomy with topical estrogen lead to successful management.